Center for social innovation - Center for social innovation
Before you get in too deep, you might want to know what we mean by “social innovation.” At CSI, we define social innovation as the creation, development, adoption, and integration of new and renewed concepts, systems, organizations and practices that put people and planet first. At their best, social innovations address root causes and change the very systems resisting change to unlock a better world for all. Social innovators achieve change by nudging and sometimes radically shifting markets, policies and cultures. Put simply, social innovation is about new solutions for a better world. We see them everywhere!
Keywords: Canada; OBNL